1986
DOI: 10.1002/pola.1986.080241129
|View full text |Cite
|
Sign up to set email alerts
|

A positron annihilation lifetime study of isotactic polypropylene

Abstract: SynopsisPositron lifetime studies were performed on well-characterized annealed and quenched samples of isotactic polypropylene. The positron experiments were conducted from -20 to 110°C a s a function of both heating and cooling. Of the three decaying exponential components resolved from the lifetime spectra, only the long-lifetime ortho-positronium (o-Ps) pickofr component was affected by the changes in temperature. The behavior of both the lifetime and intensity of the o-Ps component was interpreted with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…The measurements by Nakanishi et al [164] have shown that the o-Ps intensity I 3 changes linearly with the degree of crystallinity in poly(etherether-ketone), a similar result was obtained by Lind et al [165] in polypropylene. This can be an indication that in the crystalline part positronium does not form; it locates in the amorphous part only.…”
Section: Lifetime Nssupporting
confidence: 68%
“…The measurements by Nakanishi et al [164] have shown that the o-Ps intensity I 3 changes linearly with the degree of crystallinity in poly(etherether-ketone), a similar result was obtained by Lind et al [165] in polypropylene. This can be an indication that in the crystalline part positronium does not form; it locates in the amorphous part only.…”
Section: Lifetime Nssupporting
confidence: 68%
“…Nakanishi et a1. 16 found that 73 remained constant as a function of crystallinity in PEEK as did Lind et al 33 in polypropylene. The constant 73 result in PEEK, in addition to the result that I;'"'"" extrapolated to zero at 100% crystallinity (mentioned earlier), was interpreted to mean that there were no sized oPs free volume cavities in the crystalline region of the system.16 While this is more than likely, there is a possibility that similar r3-sized holes exist in both the amorphous and crystalline phases and, thus, annealing to increase crystallinity would not influence the value of 73. It is claimed that the longest lived (oPs) component is affected by degree of crystallinity, either due to a crystalline contribution to free volume or due to physical constraints imposed by crystals; this claim will be discussed further during the presentation of results.…”
Section: E T H O D Of Data Analysismentioning
confidence: 74%
“…This value agrees with that obtained by nuclear magnetic resonance, diatometry, and dynamic mechanical relaxation. [17][18][19] The observed temperature dependence of t 3 means the increase in the size of the open spaces by the cooperative Lind et al 9 reported measurements of lifetime cycle with a cooling rate of 10ЊC/min. In Figure 3, distinct exothermic peaks were observed in the temperature range between 380 and 400 K. Because I 3 decreases with increasing X C for polymers, 21-23 the observed discontinuous decrease of I 3 can be associated with the formation of crystalline regions and the resultant decrease in the concentration of the open spaces.…”
Section: Methodsmentioning
confidence: 99%
“…Isotactic PP is known to exhibit typically two glass transitions. 9,24 The upper and the lower glass transition temperatures were associated with onset temperatures of the molecular motions posed by the crystalline regions and those in the regions free from the constraint, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation